Stages of Gynaecological Cancers at the Time of First Presentation at a Large Cancer Hospital in Pakistan: An Observational Study - Meharunnissa Khaskheli; Shahla Baloch; Shamsunnissa Khaskheli; Ramsha Zafar Durrani; Naseema Jhatial; Syed Ghulam Sarwar Shah (Dubai Medical Journal)
Objectives: The aim was to study the types of gynaecological cancers and their stages at the time when patients first presented at the cancer registry of a major cancer hospital. Methods: This observational study was carried out in a large cancer hospital in Pakistan. We analysed secondary data on new cases of gynaecological cancer without age restriction of the patient. Fully anonymised data were obtained retrospectively from the cancer registry for 3 years from 01 January 2018 to 31 December 2020. Data were analysed for frequencies and descriptive statistics using SPSS. Results: A total of 285 new cases of gynaecological cancer were registered in the cancer registry during the study period. The patients had a median age of 52 years (mean 51.3, SD 15.7), and all had no education. Ovarian cancer was the most common gynaecologic cancer (57.9%, n = 165), followed by cervical cancer (25.9%, n = 74), uterine (endometrial) cancer (10.9%, n = 31), vaginal cancer (3.9%, n = 10), and choriocarcinoma (1.4%, n = 4). About 32% of the patients had stage 1 cancer (n = 89), 37.5% had stage 2 cancer (n = 105), 25.7% had stage 3 cancer (n = 72), and 5% had stage 4 cancer (n = 14). Conclusion: Ovarian, cervical, uterine, and vaginal cancers are the most prevalent gynaecological cancers. In Pakistan, women with gynaecological cancers, especially those who are uneducated and live in rural areas, attend tertiary care cancer hospitals with advanced cancers that can have a poor prognosis.